Can Solar Lanterns Improve Youth Academic Performance? : Experimental Evidence from Bangladesh - Kudo, Yuya (World Bank, Washington, DC, 2017)
This study conducted an experimental intervention in unelectrified areas of northern Bangladesh to investigate the effectiveness of solar products in improving children's educational achievement. It found that treated households substituted solar lanterns for kerosene-based lighting products, helping to decrease total household expenditure. Solar lanterns increased the children's home-study hours, particularly at night and before exams. The solar lanterns initially led to an increase in school attendance, but this effect diminished over time. However, the increased study hours and initial improvement in school attendance did not translate into improved academic performance. Varying the number of solar products within the treated households did not alter these results. Analyses that exploited the school grade treatment intensity also provided no evidence suggesting that spillover effects explained the "no academic performance effects." These findings suggest that improving the home-study environment solely through the provision of solar products may have a limited impact on children's educational achievement.